Peran Lembaga Keuangan Syariah dalam Meningkatkan Perekonomian Melalui Pembiayaan Modal Kerja Pada UMKM di Jepara - Farizki, Indhona Lukman; Ansori, Miswan (Al-Sharf: Jurnal Ekonomi Islam, 2024)
Islamic financial institutions, such as Islamic banks and non-bank financial institutions adhering to Sharia principles, play a crucial role in providing financial solutions that comply with Islamic guidelines. This research aims to understand the role of Islamic financial institutions in enhancing the economy through working capital financing for SMEs in Jepara. This study employs a qualitative approach, utilizing interviews and documentation for data collection. The data analysis technique used is the interactive analysis model. The results of this research conclude that there are three significant roles of Islamic Financial Institutions in boosting the economy through working capital financing for SMEs in Jepara: 1) Providing halal and interest-free working capital, 2) Enhancing the capacity and competence of SMEs, and 3) Promoting local economic development and job creation.